1989
DOI: 10.1093/bja/62.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Pulmonary Oedema Precipitated by Induction of Anaesthesia

Abstract: Neurogenic pulmonary oedema is a recognized complication of central nervous system injury. A case is presented where this condition was precipitated by induction of anaesthesia in a child with spina bifida, hydrocephalus and a malfunctioning ventriculo-peritoneal shunt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Most initial reports associated neurogenic pulmonary oedema as being precipitated by head injuries,2-4 a finding emphasised by a report of 56 casualties from the Vietnam war with major head trauma that describes evidence of pulmonary oedema in 17 patients.5 Isolated head injury is still the commonest association, but a variety of other precipitants have been reported including epilepsy,6-9 subarachnoid haemorrhage,'0-12 cerebral emboli,'3 and induction of anaesthesia. 14 The incidence is hard to determine as less severe cases may be unrecognised or attributed to aspiration. Graf and Rossi identified only two cases from a review of 2 100 head injuries,'5 but a more recent report gives an incidence of 0.62% in isolated head injuries,'6 and one intensive care unit dealt with 20 Although many of the case reports involve children or young adults,3 11 14 18 19 a review of 20 patients'7 had an age range of 11 to 71 and demonstrated no clear relation to age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most initial reports associated neurogenic pulmonary oedema as being precipitated by head injuries,2-4 a finding emphasised by a report of 56 casualties from the Vietnam war with major head trauma that describes evidence of pulmonary oedema in 17 patients.5 Isolated head injury is still the commonest association, but a variety of other precipitants have been reported including epilepsy,6-9 subarachnoid haemorrhage,'0-12 cerebral emboli,'3 and induction of anaesthesia. 14 The incidence is hard to determine as less severe cases may be unrecognised or attributed to aspiration. Graf and Rossi identified only two cases from a review of 2 100 head injuries,'5 but a more recent report gives an incidence of 0.62% in isolated head injuries,'6 and one intensive care unit dealt with 20 Although many of the case reports involve children or young adults,3 11 14 18 19 a review of 20 patients'7 had an age range of 11 to 71 and demonstrated no clear relation to age.…”
Section: Discussionmentioning
confidence: 99%
“…14 The incidence is hard to determine as less severe cases may be unrecognised or attributed to aspiration. Graf and Rossi identified only two cases from a review of 2 100 head injuries,'5 but a more recent report gives an incidence of 0.62% in isolated head injuries,'6 and one intensive care unit dealt with 20 Although many of the case reports involve children or young adults,3 11 14 18 19 a review of 20 patients'7 had an age range of 11 to 71 and demonstrated no clear relation to age. There is also no literature documenting any other association such as preceding alcohol or drug ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence exists that PEEP has a deleterious effect on intracranial pressure, its successful use and necessity in the management of children with NPO has been reported (Cohen, Gambill & Eggers 1977;Kosnick et al 1977;Milley, Nugent & Rogers 1979;Braude & Ludgrove 1989;Pender & Pollack 1992). Measures to decrease intracranial pressure including hyperventilation, osmotic and loop diuretics, elevation of the head, sedation, muscle relaxation, and anticonvulsants have all been reported in the management of children with NPO (Cohen, Gambill & Eggers 1977;Kosnick et al 1977;Milley, Nugent & Rogers 1979;Braude & Ludgrove 1989;Pender & Pollack 1992). In addition to these medical interventions, neurosurgical drainage of epidural, subarachnoid, or intraventricular blood or CSF may be required urgently to decrease intracranial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported to occur during the induction of anaesthesia in a child scheduled to have a malfunctioning ventriculoperitoneal shunt revised(Braude & Ludgrove 1989). The pathogenesis of neurogenic pulmonary oedema has been extensively reviewed(Luisada 1967; Theodore & Robin 1975;Kosnick et al 1977; Lough- nan et al 1980;Colice et al 1984; …”
mentioning
confidence: 99%
“…Methods: The current body of literature, partially obtained by computer-guided search (Winspirs) regarding epidemiology, pathophysiology and therapy of NPE was reviewed.Additionally, the case of a patient who developed a sudden pulmonary edema after an episode of tonic-clonic seizures is analyzed.We first provide information about history, definition, incidence and mortality of NPE.Second, a case report of a postictal NPE is presented to illustrate the clinical picture of NPE, and the applied therapeutic strategies are discussed.Third, recent pathophysiologic concepts about symptoms and possible therapeutic principles are reviewed.Fourth, a rational therapeutic plan for the prehospital emergency therapy of NPE is outlined. Results: The different ethiologies all have one characteristic feature:an acute emergency which causes increased intracerebral pressure (ICP).NPE is known in patients after cerebral trauma, intracranial hemorrhage, stroke, intracranial tumor or seizures.The incidence is estimated at around 1% after cerebral trauma, at 71% after cerebral hemorrhage and at 2% after seizures.Mortality is appraised to lie between 60 and 100%, independent of etiology.There is a definite pathophysiologic sequence leading to NPE: a central nervous system lesion causes a sudden increase in ICP which triggers an upregulation of sympathetic signal transduction to assure brain perfusion.Increased tonus of venous and arterial vessels and of myocardial function are the immediate consequences.However, if systemic vascular resistance (SVR) increases excessively, left ventricular failure and finally pulmonary edema (NPE) may result.Additionally, the protein-rich edema fluid points to an increased endothelial permeability within the pulmonary circuit.This is thought to be caused by the acute pressure increase and by len Läsionen [19,51], bei Multipler Sklerose [36,103,110], nach Narkotika [9,11], nach Trigeminusblockade [125], ausgelöst durch ein Ödem der Medulla oblongata [10], bzw. Hirnstammläsionen [52], sowie infolge eines Hirnödems bei Hö-henkrankheit [57], Marathonlauf [126] oder nach Hypoxie bei Myokardinfarkt [81].…”
Section: Zusammenfassungmentioning
confidence: 99%